2014
DOI: 10.1353/cpr.2014.0032
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Tobacco Cessation and Smoke-Free Workplaces Through Community Outreach Partnerships in Puerto Rico

Abstract: Background Puerto Rico (PR) has a lower smoking prevalence than the United States (14.8% vs. 21.2%, respectively); nevertheless, the five leading causes of death are associated with smoking. There is a need to implement evidence-based tobacco control strategies in PR. Objectives The Outreach Pilot Program (OPP) was designed to engage communities, health professionals, and researchers in a network to advance health promotion activities and research to increase the use of the PR Quitline (PRQ) among smokers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 58 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Also, the Community Outreach Heart Health and Risk Reduction Trial for high-risk subjects with primary or secondary cardiovascular events reported that telehealth lifestyle counseling was more effective at decreasing blood pressure or cholesterol than the recommended guideline for six months [28]. [29]. Similarly, the community outreach for smoking cessation in India was conducted [30].…”
Section: For Lifestyle Changementioning
confidence: 99%
“…Also, the Community Outreach Heart Health and Risk Reduction Trial for high-risk subjects with primary or secondary cardiovascular events reported that telehealth lifestyle counseling was more effective at decreasing blood pressure or cholesterol than the recommended guideline for six months [28]. [29]. Similarly, the community outreach for smoking cessation in India was conducted [30].…”
Section: For Lifestyle Changementioning
confidence: 99%
“…Collaboration among multisector organizations is essential in addressing the gaps in tobacco control and other public health issues. 36 The absence of collaboration can constrict the reach and impact of public health initiatives. For instance, barriers to enforcement of illicit tobacco trade emerge from a lack of partnership and trust between different organizations and can be overcome by partnerships between health, marketing, and enforcement agencies.…”
Section: Social Processesmentioning
confidence: 99%
“…34,46 Numerous studies mention community mobilization as a means to empower communities to impact social and health issues as well as an outcome of multisector collaboration. [30][31][32][33]35,36,44,45 It is a key enabler of convergent innovation especially in a technologically-savvy world where Internet and mobile connectivity facilitate better and quicker organization of communities. 18 Communities are best aware of their needs as well as their strengths, and once engaged, resourced, and mobilized, they can become an impetus for sustained convergent innovation and impact.…”
Section: Organizational and Institutional Processesmentioning
confidence: 99%
See 2 more Smart Citations